KALMAN FILTER SEBAGAI METODE ESTIMASI UNTUK MENGUKUR KECEPATAN KENDARAAN - Romi Wiryadinata (Faculty of Industrial Technology Universitas Islam Indonesia, 2014)
Methods for estimating speed be categorized into two classes, namely active method and passive methods. One method that can be used in speed estimation using a passive method is the Kalman filter. Kalman filter is an very effective estimator that is in estimating state dynamics system involving white noise. In this study, the Kalman filter will be used to estimate the variation of vehicle speed from a speed of 5 km/hour to 60 km/hour. Kalman filter is designed to get input in the form of cascading imagery of the vehicle video recordings. Results of the testing showed that speed can be minimum estimated is 20 km hour with an error of 4.25%. While the maximum estimated speed is 60 km/hour with an error of 0.22%.